Structural Properties of Silicon Doped Rare Earth Elements Ytterbium - Khodjakbar S. Daliev; Sharifa B. Utamuradova; Jonibek J. Khamdamov; Mansur B. Bekmuratov (East European Journal of Physics, 2024)
This paper presents the results of a study of the state of ytterbium atoms in silicon, carried out using the methods of Fourier transform infrared spectroscopy (IR) and Raman spectroscopy (RS). Silicon samples doped with ytterbium impurities were analyzed using FSM-2201 and SENTERRA II Bruker spectrometers. Registration and identification of both crystalline and amorphous phase components in the samples was carried out. The results of the study confirm that doping silicon with ytterbium impurities leads to a decrease in the concentration of optically active oxygen  by 30-40%, depending on the concentration of the introduced impurities. It was also found that an increase in the number of defects leads to a broadening of the amorphous zone. It is assumed that similar dependencies exist for the Si-Yb system; however, to the best of our knowledge, similar results have not been reported previously. It is noted that the relative intensity of the three Raman bands in Si-Yb systems in the LTIOS (The light and temperature induced ordered state) state changes, and the relative intensity of Si-Si decreases. This indicates that pendant bonds are mainly formed by the breaking of Si-Si bonds. It was also observed that the light intensity causing this condition is far from that required for laser or solid phase crystallization. Using the Raman spectroscopy method, a structural transformation was discovered, expressed in a densely packed array of nanocrystals with a size of less than 11 lattice parameters. Small clusters were under strong internal stress (up to 3 GPa), which probably prevents the cluster size from increasing beyond the critical value for irreversible crystallization.